Firm exit and armed conflict in Colombia - Andriana Camacho; Catherine Rodriguez (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper uses two unique panel data sets to study the causal effect that armed conflict has over entrepreneurial activity in Colombia. Using a fixed effect estimation methodology at the plant level and controlling for the possible endogeneity of armed conflict through the use of instrumental variables, we find that a one standard deviation in the number of guerrilla and paramilitary attacks in a municipality increases the probability of firm exit in 8.1 percentage points. This effect is stronger for smaller plants and has a differential impact with respect to firms' age.
Keywords: D21; J31; R30; 330; conflict; firm exit; entrepreneurship; Colombia